Ultra-Broadband Polarization Beam Splitter Based on Cascaded Mach-Zehnder Interferometers Assisted by Effectively Anisotropic Structures - Zongxing Lin; Kaixuan Chen; Qiangsheng Huang; Sailing He (IEEE Photonics Journal)
An ultra-broadband polarization beam splitter (PBS) consisting of cascaded Mach-Zehnder interferometers (MZIs) is proposed on 220 nm-thick silicon-on-insulator (SOI) platform. The configuration of the cascaded MZIs has a point symmetry in order to broaden the bandwidth of the cross-coupling for the TM polarization. The sub-wavelength grating (SWG) structures act as effectively anisotropic cladding to enhance the separation of the two fundamental polarizations. Two filters with cascaded bends and a Bragg reflection structure at the two outputs, respectively, are used to further improve the extinction ratio (ER). The proposed PBS has a remarkable performance with ER > 20 dB over a record broad bandwidth of 310 nm (IL < 0.5 dB) or 350nm (IL < 1 dB) for both TE and TM polarization inputs.